Patient load and spectrum of dental problems amongst the population attending outpatient services of a tertiary care medical college hospital, Arunachal Pradesh - Tumbi Lollen; TageTamo; Moji Jini; Boro, Pallavi; Naba Jyoti Saikia (Asian Journal of Medical Sciences, 2022)
Background: Evidences suggest relationship between periodontitis and systemic diseases such as cardiovascular diseases, diabetes mellitus, adverse pregnancy outcome, osteoporosis and chronic kidney diseases. Except for acute toothache and complicated local infection, other dental problems are often considered trivial, hence dental health is often neglected or omitted in health related discourses. Aims and Objectives: (1) To assess the patient load in dental OPD compared to other outpatient departments and (2) examine the distribution of dental diseases among different age, gender and caste of dental patients in a tertiary care hospital over a 5 year period. Materials and Methods: A hospital based retrospective study was conducted using data from Medical Record department of all OPD attendees (1,174,605) during the period from January 2016 to December 2020 in the tertiary care hospital of Arunachal Pradesh. The total number of dental OPD patients (57,198) was compared with the total and department wise OPD attendees during the same period. Out of all Dental patients , data of 11,225 were found to be complet ( cross checked MRD record with OPD register) hence analysed for distribution of disease as per age/ sex/ ethnicity. Results: Emergency and Casualty department reported highest patient load, lowest in cardiology. Overall dental patient OPD load was highest in 2019 and lowest in 2020. Common dental problems were caries and its complications, root stamp/retained tooth, dental calculus, stain, and trauma related dental problems. Most of the trauma related cases were males, whereas other conditions like dental caries, root stamp, complication of caries, and dental calculus/stain were more common in females. Conclusion: Data shows that the number of dental patients among all OPD attendees is high and the dental problems they present with are diverse in nature. The treatment provisions available in most health care centres are largely inadequate. Inclusion of Oral and Dental health in Planning of community health programs, sensitisation of all health care providers the importance of interdepartmental consultation with dental department and education of the masses in oral and dental care/hygiene are of paramount importance.